2018
DOI: 10.12968/pnur.2018.29.10.465
|View full text |Cite
|
Sign up to set email alerts
|

Management of asthma: Adherence, inhaler technique and self-management

Abstract: Asthma is defined as a chronic inflammatory disorder of the airways associated with an increase in airway hyper-responsiveness that leads to recurrent episodes of wheezing, breathlessness, chest tightness and coughing (particularly at night). When control is achieved, patients can avoid these symptoms, exacerbations, side effects of treatment and lead an active life. The fundamental components to achieving this is adherence to inhaled therapies, optimising inhaler technique and engaging the patient in self-man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…[ 2 ] Different factors affect asthma control, such as a patient’s medication knowledge, adherence and appropriate inhaler techniques. [ 3,4 ] Poor medication knowledge leads to wrong beliefs that further affect patients' adherence to medication. [ 5 ] Poor adherence is linked to poor disease outcomes such as increased mortality, increased cost and increased rate of hospital admission.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] Different factors affect asthma control, such as a patient’s medication knowledge, adherence and appropriate inhaler techniques. [ 3,4 ] Poor medication knowledge leads to wrong beliefs that further affect patients' adherence to medication. [ 5 ] Poor adherence is linked to poor disease outcomes such as increased mortality, increased cost and increased rate of hospital admission.…”
Section: Introductionmentioning
confidence: 99%
“… 31 One study indicated that detecting patients’ non-adherence behaviours and appreciating their self-management may help to change their behaviour and increase adherence. 35 On the other hand, patients think that their physicians did not have enough time or provide enough information to them, which contributed to patients lack of sufficient knowledge of the importance of treatment adherence to controlling their asthma. 22 , 29 A systematic review reported that patient–provider interactions was significantly related to treatment adherence and patient health outcomes; 36 so it is likely that adherence would increase if the rationale of the treatment plan was explained in a way that patients can understand and follow.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Patients reported that the lack of self-efficacy to recognise their asthma symptoms and also to distinguish these accurately from other symptoms, such as breathlessness caused by physical exertion, prevented them from the appropriate use of medication and from avoiding triggers [92]. Depending on the patient's level of knowledge, self-efficacy to self-manage and their illness perception, a stratified combination of asthma education with checking correct inhaler technique, good HCP-patient relationship and interventions to increase patients' motivation to self-manage, can be beneficial to improve treatment adherence [92,93]. Indeed, written or oral asthma action plans, that is detailed plans for self-management including actions when asthma worsens, also showed some benefits, but further research is needed to fully understand their most effective components, their implementation barriers and facilitators both from patients' and healthcare professionals' points of view [94,95].…”
Section: Educational Approachesmentioning
confidence: 99%